Dynamic changes in the endophytic bacterial communities of huanglongbing-affected periwinkle leaves - Liu, Xiaofei; Dai, Yuli; Gan, Lin; Lan, Chengzhong; Ruan, Hongchun; Zheng, Lizhen; Zheng, Yu; Gan, Yun; Yang, Xiujuan (Frontiers in Microbiology, 2025)
The pathogenetic mechanism of citrus huanglongbing (HLB) disease caused by Candidatus Liberibacter asiaticus (Clas) remains unclear, particularly its association with host-related microbial communities. It has been demonstrated that HLB infection alters endophytic bacteria, which may be the cause of disease initiation. In this study, periwinkle plants were used as a model and uniformly inoculated by grafting with HLB-infected citrus shoots. Leaf samples were collected at 30, 60, and 90 days post-inoculation (dpi) to assess alterations in endophytic bacterial communities using high-throughput sequencing, and uninfected periwinkle plants served as controls. Across all samples, 24 bacterial phyla and 300 genera were identified. In healthy plants, the endophytic bacterial diversity and richness remained relatively stable over time, with Arcobacter, Pseudomonas, and Giesbergeria identified as the predominant genera. In contrast, HLB-infected plants exhibited a marked decline in bacterial diversity over time, though richness was not significantly affected. Notably, the relative abundance of Candidatus Liberibacter increased significantly, and it became the dominant genus by 30 dpi, followed by Arcobacter and Pseudomonas. HLB infection was also associated with a sustained reduction in abundance of certain genera, including Anaerovorax, Neisseria, and Paeniclostridium. This study provides a detailed overview of the temporal dynamics of leaf endophytic bacterial communities following HLB infection of periwinkle plants. This study enhances our understanding of host–microbe–pathogen interactions and may guide future studies aiming to select useful microbial candidates for HLB alleviation and plant resilience.